Influence of Active Channel Layer Thickness on SnO2 Thin-Film Transistor Performance - Do Won Kim (Electronics, 2021)
Sol-gel processed SnO2 thin-film transistors (TFTs) were fabricated on SiO2/p+ Si substrates. The SnO2 active channel layer was deposited by the sol-gel spin coating method. Precursor concentration influenced the film thickness and surface roughness. As the concentration of the precursor was increased, the deposited films were thicker and smoother. The device performance was influenced by the thickness and roughness of the SnO2 active channel layer. Decreased precursor concentration resulted in a fabricated device with lower field-effect mobility, larger subthreshold swing (SS), and increased threshold voltage (Vth), originating from the lower free carrier concentration and increase in trap sites. The fabricated SnO2 TFTs, with an optimized 0.030 M precursor, had a field-effect mobility of 9.38 cm2/Vs, an SS of 1.99, an Ion/Ioff value of ~4.0 × 107, and showed enhancement mode operation and positive Vth, equal to 9.83 V.